2022
DOI: 10.1101/2022.12.30.22283949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On temporal changes in the role of different age groups in propagating the Omicron epidemic waves in England

Abstract: Background: There is limited information on the role of individuals in different age groups in the spread of infection during the Omicron epidemics, especially ones beyond the winter epidemic wave in 2021-2022. COVID-19 booster vaccination in England during the Autumn 2022 was restricted to persons aged over 50y, and persons in clinical risk groups. Methods: We used previously developed methodology to evaluate the role of individuals in different age groups in propagating the Spring, Summer, and Autumn waves o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The role of individuals in different age groups during the subsequent waves of Omicron epidemics is less studied. In our companion paper [9], we showed that as time progressed, the leading relative role in propagating the Omicron epidemic waves in England shifted from school-age children to younger adults to adults aged 35-44y and 65-74y. In this paper, we applied the previously developed methodology [14-16,3,4] to study the relative role of individuals in different age groups during the Spring, Summer, Autumn and Autumn-Winter waves of the 2022 Omicron epidemic in France.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The role of individuals in different age groups during the subsequent waves of Omicron epidemics is less studied. In our companion paper [9], we showed that as time progressed, the leading relative role in propagating the Omicron epidemic waves in England shifted from school-age children to younger adults to adults aged 35-44y and 65-74y. In this paper, we applied the previously developed methodology [14-16,3,4] to study the relative role of individuals in different age groups during the Spring, Summer, Autumn and Autumn-Winter waves of the 2022 Omicron epidemic in France.…”
Section: Discussionmentioning
confidence: 99%
“…This method was also used in the context of SARS-CoV-2 epidemics in 2020 and 2021 to show the prominent relative role of younger adults and older adolescents in the transmission process [4,5]. In our companion paper [9], we showed that as time progressed, the leading relative role in propagating the Omicron epidemic waves in England shifter from school-age children to younger adults to adults aged 35-44y and 65-74y. In this paper we use the RR statistic to examine the role of individuals in different age groups during four waves of the Omicron epidemic in France between March 1, 2022 and Dec. 29, 2022.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations